APPLICATION OF ADDITIONAL CORRECTIVE CRIMINAL PENALTIES IN ENVIRONMENTAL CRIMES ( CASE STUDY OF BALIGE DISTRICT COURT DECISION NO. 28 /PID.SUS/201 5 /PN .BLG ) - Tabroni (Judge : Jurnal Hukum, 2025)
The background of this research is the increasing threat to environmental sustainability due to human activities. Law Number 32 of 2009 concerning Environmental Protection and Management (UUPPLH) serves as the legal basis, which allows for the imposition of principal and additional criminal sanctions on business entities committing environmental crimes. The case in question involves PT. Gorga Duma Sari (PT. GDS), where its president director, JONNI SIHOTANG, was accused of environmental damage through tree felling and land clearing without permits and valid environmental documents, causing damage to the river ecosystem. Although the Public Prosecutor did not demand additional remedial penalties, the Panel of Judges at the Balige District Court in its decision imposed additional penalties on PT. GDS to repair the environmental damage. This decision was based on the consideration that the crime was committed for the benefit and profit of PT. GDS, as well as the application of the principles of "Polluter Pays" and "In Dubio Pro Natura" through judicial activism. This research highlights the differences in views between the demands of the Public Prosecutor and the judge's decision, which was ultra petita in applying additional remedial criminal sanctions. The conclusion of the research shows that the basis for the judge's consideration in imposing additional penalties is because the crime was committed for and on behalf of PT. GDS which received the profits, based on Article 116 paragraph (1) in conjunction with Article 118 in conjunction with Article 119 of the UUPPLH and the principles of "Polluter Pays" and "In Dubio Pro Natura". This research also suggests optimizing the demands for additional criminal improvements by the public prosecutor in environmental crime cases.